The Effect of Moderate Intensity Swimming Exercise on Antioxidant Enzyme Activity Levels in Adults - Nadhila Diamanda, Jihan; Wahyuni, Nila; Eka Darwinata, Agus (International Journal of Health and Pharmaceutical (IJHP), 2026)
This study aimed to investigate the effect of moderate intensity swimming exercise on the activity levels of antioxidant enzymes in adults. To achieve this, a literature review was conducted, analyzing data from multiple studies examining the impact of regular swimming on antioxidant markers such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). The studies included in the review varied in terms of participant demographics, exercise protocols, and measurement techniques. The findings consistently showed that moderate intensity swimming exercise significantly enhances the activity of key antioxidant enzymes, indicating an improved oxidative stress response. This suggests that engaging in regular moderate intensity swimming can be a beneficial strategy for bolstering the body's antioxidant defenses, potentially contributing to better overall health and reduced risk of oxidative stress-related diseases.